The Ancient Egyptian Footwear Project : final archaeological analysis - Veldmeijer, A. J. (Sidestone Press, 2019)
The Ancient Egyptian Footwear Project (AEFP) is a multidisciplinary, ongoing research of footwear in ancient Egypt from the Predynastic through the Ottoman Periods. It consists of the study of actual examples of footwear, augmented by pictorial and textual evidence. This volume evaluates, summarises and discusses the results of the study of footwear carried out by the AEFP for the last 10 years (which includes the objects in the major collections in the world, such as the Egyptian Museum in Cairo, the British Museum in London and the Metropolitan Museum in New York, as well as from various exc.